Engineering students' learning during internships: Exploring the explanatory power of the job demands‐control‐support model. Issue 2 (28th January 2020) - Goller, Michael; Harteis, Christian; Gijbels, David; Donche, Vincent
Abstract: Background: Internships are highly relevant learning experiences for engineering students. However, such practice‐based learning settings must be carefully designed to allow their learning potential to unfold. Purpose: Exploring the job demands‐control‐support (JDCS) model, this study aimed to investigate how job demands, job control, and social support affect interns' use of different learning strategies. Method: The study utilized data collected from a sample of engineering students ( n = 118) who completed a required internship during their degree. The data were analyzed using a structural equation modeling approach including latent factors. Results: Job demands were found to be a relevant and significant driver of students' shared regulation (e.g., asking for feedback), self‐regulation (e.g., self‐directed use of codified information), efforts to relate theory to practice (e.g., connecting workplace experience with theoretical knowledge), and the absence of avoidance of learning (e.g., lack of adaptation to work situations), but not of external regulation (e.g., asking for help to solve problems). Job control, however, was not found to be a positive or significant driver of student learning. Social support was found to be a relevant and significant predictor of external and shared regulation but not of the other learning activities. Conclusions: This study provided mixed findings regarding key hypotheses central to the JDCS model, generating rather poor evidence supporting it. In fact, job demands, job control, and social support exhibited much less explanatory power than expected for engineering students' learning during internships.